Optimization of culture conditions for mycelial growth, fruiting body production, and biological properties of volvariella volvacea (paddy straw mushroom) from the Philippines - Tapnio, Louie Santos (Animo Repository, 2023)
Volvariella volvacea (Bull.: Fr.) [Plutaceae] is among the commonly cultivated mushrooms yet an established protocol for its cultivation from mycelia to fruiting bodies is still wanting. Six isolates of the Volvariella volvacea were evaluated based on their mycelial growth on different culture media, pH, temperature, light and aeration requirements. Their fruiting performance on supplemented substrates, and subsequent nutrient composition, mycochemical compounds and antioxidant activities of the fruiting bodies were also evaluated. All isolates exhibited significant growth differences across both commercial and indigenous media. San Jose (SJ) and Brgy. Rang-ayan Muñoz, Nueva Ecija (VVA) isolates showed efficient mycelial growth on commercial Potato Dextrose Agar (PDA), while Tarlac (TC), La Union (LU), CLSU (VVB), and San Mateo Rizal (SP) isolates on indigenous Corn Grit Decoction Gulaman (CGDG). Significant growth differences were observed across all pH, with most isolates preferring alkaline medium except the SJ isolate that preferred the acidic medium (pH 5). Most isolates showed no significant mycelial growth under both lighted and dark conditions except the TC isolate that grew best on dark condition. VVA and SP grew best on sealed conditions while the rest of the isolates showed no significant growth differences on both sealed and unsealed conditions. All isolates showed good mycelial growth at 30-32oC and no growth at 6-9oC (refrigerated condition). Supplementation of rice bran or coconut water on banana leaves were found to enhance the fruiting performances of all isolates. The proximate analysis of the fruiting bodies revealed promising amount of minerals (ash), protein, fiber, carbohydrates, and low fat content. Only SJ and TC isolates yielded both flavonoids and alkaloids. Varying levels of antioxidant activities ranging from 38.44±1.76 to 52.68±2.35 were recorded. However, DPPH scavenging activities for all isolates were found lower than the control catechin (82.24±0.30%). This research corroborated the previous findings that the conditions for mycelial growth and fruiting body production in V. volvacea is isolate-dependent.